The Influence of Religion on the Criminal Behavior of Emerging Adults - Salvatore, Christopher (Religions, 2018)
Recent generations of young adults are experiencing a new life course stage: emerging adulthood. During this new' stage of the life course, traditional social bonds and turning points may not be present, may be delayed, or may not operate in the same manner as they have for prior generations. One such bond, religion, is examined here. Focusing on the United States, emerging adulthood is investigated as a distinct stage of the life course. The criminality of emerging adults is presented, a theoretical examination of the relationship between religion and crime is provided, the role of religion in emerging adults' lives is explored, research on the role of religion's influence on criminal offending is presented, and theoretical and policy implications are offered.